2019
DOI: 10.21705/mcbs.v3i2.56
|View full text |Cite
|
Sign up to set email alerts
|

Association between Hasford Scoring System and Hematologic Response in Chronic and Accelerated Phase of Chronic Myelocytic Leukemia Patient with Imatinib for Three Months

Abstract: Background: Hasford score is a scoring system which was made in interferon treatment era to assess chronic myelocytic leukemia (CML) prognosis. Complete hematologic response (CHR) is the milestone of prognosis evaluation. CHR achievement will significantly increase survival. Imatinib is a revolutionized treatment that change the prognosis of CML. With the advent of Imatinib, lessened the prognostic impact of the Hasford score to predict prognosis.Materials and Methods: An observational analytic with prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…Some of them are leukocyte count, leukocyte differential count (basophil, eosinophil, neutrophil, lymphocyte, and monocyte), neutrophil to lymphocyte ratio (NLR), monocyte to lymphocyte ratio (MLR), and erythrocyte sedimentation rate (ESR). (3,6,16,17) At the present time, the role of serum ADA and hematological tests in ITB patients are not widely known. The objective of this study was to determine the role of ADA and hematological tests in patients suspected with ITB.…”
Section: Resultsmentioning
confidence: 99%
“…Some of them are leukocyte count, leukocyte differential count (basophil, eosinophil, neutrophil, lymphocyte, and monocyte), neutrophil to lymphocyte ratio (NLR), monocyte to lymphocyte ratio (MLR), and erythrocyte sedimentation rate (ESR). (3,6,16,17) At the present time, the role of serum ADA and hematological tests in ITB patients are not widely known. The objective of this study was to determine the role of ADA and hematological tests in patients suspected with ITB.…”
Section: Resultsmentioning
confidence: 99%
“…However, other studies showed different results, such as differences in white blood cells and hemoglobin at baseline before reaching CHR [ 47 ]. Although prognostic score systems in CML, including Sokal et al [ 30 ], Hasford et al [ 31 ], and EUTOS were developed to predict major molecular response and complete cytogenetic response, several studies also investigated their relationships with CHR [ 48 , 49 ]. Patients with low Sokal et al [ 30 ] and Hasford et al [ 31 ] scores were more likely to achieve CHR [ 49 ].…”
Section: Discussionmentioning
confidence: 99%